REVEALING THE VALUE RELEVANCE OF ACCOUNTING INFORMATION AND DECISION TO PURCHASE SHARES (PHENOMENOLOGY STUDY ON INCREASING SHARE PRICES PT. ANTAM, TBK IN THE PANDEMIC COVID-19): PHENOMENOLOGY STUDY ON INCREASING SHARE PRICES PT. ANTAM, TBK IN THE PANDEMIC COVID-19 - Warae, Ya'atulo (Archives of Business Research, 2021)
Investing in stocks is a very tempting part for investors to increase the amount of income significantly. Stock investment decisions are influenced by the development of information around investors, either direct information or information that is not directly related to the company. The purpose of this study is to determine the essence of the value relevance of accounting information in making stock investment decisions during the Covid-19 pandemic by investors of PT. Antam, Tbk, thus affecting the increase in the share price of PT. Antam, Tbk soared to 130 percent by the end of 2020. This research is a qualitative research with anphenomenological approach interpretive and data analysis methods of Miles and Huberman. Types and sources of data used in this study are primary data obtained directly from interviews with informants and observations of several important issues on news in mass media and social media. The results showed that each informant has his own perception regarding the relevance of the value of accounting information in making stock investment decisions with the aim of obtaining capital gains. The results of the analysis of the value of accounting information obtained from both financial statement analysis and analysis of other information such as positive / negative issues, news from mass media and social media are interrelated and support each other in helping investors. in producing stock investment decisions and increasing the level of confidence in these decisions in order to obtain capital gains, by always paying attention to the latest changes and developments in the capital market.